Relapse after methylprednisolone oral minipulse therapy in childhood vitiligo: A 12-month follow-up study - Imran Majid; Saher Imran (Wolters Kluwer Medknow Publications, 2013)
Background: Oral minipulse (OMP) therapy with methylprednisolone is presently one of the most common oral treatments used for progressive vitiligo in children. The treatment is usually given for a period of 6 months during which majority of patients are reported to go into remission. However, there are no follow-up studies to comment upon what happens to the disease after OMP therapy is withdrawn. Aim of the study: To document the incidence of relapse over a period of 1 year after OMP therapy is stopped in children with vitiligo. Materials and Methods: The study was conducted in 180 patients of childhood vitiligo (<15 years of age) who had been on OMP therapy with oral methylprednisolone for at least 6 months and who had achieved a complete remission of their disease during the treatment period. The enrolled patients were followed up for a period of 1 year and examined clinically for any sign of reactivation of their disease over either the old lesions or at any new area of the body. Results: Forty-two patients were lost and could not complete the follow-up period of 1 year. Out of the 138 patients available at the end of 1 year, relapse was observed in 48 patients (34.8%). Rest of 90 patients remained in remission over the follow-up period of 1 year. Relapse was more common in patients below 10 years of age (47.4%) as compared with older children (25.9%). Conclusion: Relapse after using methylprednisolone OMP therapy in children with vitiligo is quite common especially in younger age groups. Studies are needed to see whether these relapses could be avoided by giving the treatment for a period longer than 6 months.